2021
DOI: 10.3390/jcm10225460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indexes to Measure Comorbidity Burden and Predict All-Cause Mortality in Rheumatoid Arthritis

Abstract: Objectives: To examine the comorbidity burden in patients with rheumatoid arthritis (RA) patients using a nationwide population-based cohort by assessing the Charlson Comorbidity Index (CCI), Elixhauser Comorbidity Index (ECI), Multimorbidity Index (MMI), and Rheumatic Disease Comorbidity Index (RDCI) scores and to investigate their predictive ability for all-cause mortality. Methods: We identified 24,767 RA patients diagnosed from 1998 to 2008 in Taiwan and followed up until 31 December 2013. The incidence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Comorbidities may precede or appear during the course of the disease. Some studies noted that the burden of comorbidity is common before and after RA diagnosis, and the rate of accumulation accelerates after RA diagnosis [ 21 , 22 ]. Our results were close to the reported scores of RDCI in RA [ 14 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbidities may precede or appear during the course of the disease. Some studies noted that the burden of comorbidity is common before and after RA diagnosis, and the rate of accumulation accelerates after RA diagnosis [ 21 , 22 ]. Our results were close to the reported scores of RDCI in RA [ 14 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies noted that the burden of comorbidity is common before and after RA diagnosis, and the rate of accumulation accelerates after RA diagnosis [ 21 , 22 ]. Our results were close to the reported scores of RDCI in RA [ 14 , 21 ]. In this study, hypertension was the most common comorbidity as it has been reported in other studies [ 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDCI. We used patient-reported data to evaluate the burden of comorbidity across 11 comorbid conditions outlined in previous studies (19,20). Conditions included ulcer or stomach problem, hypertension, myocardial infarction, other cardiovascular disease (e.g., heart failure), lung disease, diabetes mellitus, depression, cancer, stroke, and fracture (i.e., spine, hip, or leg).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…Conditions included ulcer or stomach problem, hypertension, myocardial infarction, other cardiovascular disease (e.g., heart failure), lung disease, diabetes mellitus, depression, cancer, stroke, and fracture (i.e., spine, hip, or leg). The index was calculated based on the presence and severity of coexisting comorbid conditions, with impact assessed using 6 outcomes that were weighted as described in previous studies (15,19). The RDCI ranges from 0 to 9 and assesses quality of life and the anticipated effects of comorbidities on functional disability and mortality.…”
Section: Significance and Innovationsmentioning
confidence: 99%